(untitled) (Research, Society and Development, 2024)
Objective: To evaluate the perception of hyposalivation symptoms and their consequences in the oral cavity among adults and elderly individuals using chronic medications. Methods: A cross-sectional, descriptive study of a qualitative and quantitative nature was conducted with 15 adults over 20 years old of both genders at the Stomatology Clinic of the Federal University of Pernambuco. The stimulated sialometry test was used to measure saliva production. The Xerostomy Inventory questionnaire was used to assess xerostomia. The obtained data were analyzed descriptively. Results: The majority of the sample consisted of women over 41 years old. The most commonly used medications were antidepressants and antihypertensives. In the stimulated sialometry test, only 6.67% of participants had normal saliva production, with only one person presenting normal levels. Mild hyposalivation was found in 6.67%, moderate in 26.67%, and severe in 60%. Few respondents perceived a decrease in saliva production. Conclusion: The use of polypharmacy can lead to hyposalivation, which is associated with disturbances in the stomatognathic system. Xerostomia may not be identified early by patients, complicating adequate treatment.